Concurrent Versus Sequential Intrapleural Instillation of Tissue Plasminogen Activator and Deoxyribonuclease for Pleural Infection. Issue 2 (April 2018) - Kheir, Fayez; Cheng, George; Rivera, Estefania; Folch, Alejandro; Folch, Erik; Fernandez-Bussy, Sebastian; Keyes, Colleen; Parikh, Mihir; Channick, Colleen; Chee, Alex; Majid, Adnan
Abstract : Background: Treatment of pleural infection with instillation of sequential intrapleural tissue plasminogen activator (tPA) and human recombinant deoxyribonuclease (DNase) twice daily for a total of 6 doses has been shown to decrease surgical referral and improve radiographic imaging. This labor-intensive regimen was empirically chosen. Thus, it remains unclear whether the 2 drugs can be administered immediately one after the other (concurrent administration) instead of instilling them separately with a 1-hour to 2-hour interval in between (sequential administration). The aim of this study was to compare the efficacy and safety of sequential versus concurrent tPA/DNase therapy in patients with pleural infection. Methods: This was a prospective observational study. Consecutive patients with pleural infection who received concurrent and sequential tPA/DNase were included. The initiation and number of doses of tPA/DNase therapy were based on the amount of pleural fluid drainage, clinical response and radiographic findings. Results: A total of 38 patients with pleural infection received tPA/DNase treatment: 18 in the sequential group and 20 in the concurrent group. Treatment was successful in 77.7% in the sequential group and 75% in concurrent group ( P =0.57). There was no statistically significant difference between the 2 treatment groups (sequential and concurrent) in median pleural fluid drainage ( P =0.45), median volume of pleural effusion estimated on chest computed tomography scan ( P =0.4) or median hemithorax occupied by effusion on chest radiography ( P =0.83) following intrapleural therapy. One patient required a blood transfusion for gradual pleural blood loss in each treatment group. Pain needing escalation of analgesia affected 3 patients in each arm but none required cessation of therapy. Conclusion: A simpler regimen of concurrent administration of intrapleural tPA/DNase as compared with sequential intrapleural therapy is safe, effective, and represents a viable option for the management of pleural infection.